84.0k views
1 vote
F(x) = x2 + 6x, g(x) = x + 4(g ∘ f)(2)

F(x) = x2 + 6x, g(x) = x + 4(g ∘ f)(2)-example-1

1 Answer

7 votes

Given,

The expression is:

f(x) = x^2 + 6x

g(x) = x + 4

Required:

The value of (g ∘ f)(2).

The value of (g ∘ f)(x)


\begin{gathered} \left(g∘f\right)\left(x\right)=g(f(x)) \\ =g(x^2+6x) \\ =x^2+6x+4 \end{gathered}

The value of (g ∘ f)(x) is x^2+6x+4.

The value of (g ∘ f)(2) is,


\begin{gathered} \left(g∘f\right)\left(x\right)=x^2+6x+4 \\ (g∘f)(2)=2^2+6(2)+4 \\ =4+12+4 \\ =20 \end{gathered}

Hence, the value of (g ∘ f)(2) is 20.

User Amulya Kashyap
by
4.9k points